Beyond recognition - Pearson, Ridley (Hyperion, 1997)
There is a homicidal arsonist loose in Seattle. Single mothers are being killed in fires that burn hotter than experts have ever seen. Somehow, the children are spared. For Seattle Police Sergeant Lou Boldt and the department's psychologist, Daphne Matthews, the High Temperature Accelerant fires challenge their every resource